1980
DOI: 10.1007/bf03179150
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of carbohydrates in the heart of the scorpionHeterometrus fulvipes (C L Koch)

Abstract: The changes in the levets of total anthrone positive substances glycogen and glucose and the activities of phosphorylase, lactate dehydrogenase and succinate dehydrogenase were studied in the in situ heart of the scorpion H. fulvipes, based on the theme of acceleration and inhibition. TAPS and glucose showed appreciable depletion in the accelerated hearts and conservation in the inhibited hearts. Glycogen depletion in the accelerated hearts is not significant while conservation in the inhibited hearts is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Jayaram and Padmanabha Naidu () found that accelerated heartbeat caused glucose depletion, whereas phosphorylase increased with increasing heart beat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jayaram and Padmanabha Naidu () found that accelerated heartbeat caused glucose depletion, whereas phosphorylase increased with increasing heart beat.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylases activity was higher in males. Jayaram and Padmanabha Naidu (1980) found that accelerated heartbeat caused glucose depletion, whereas phosphorylase increased with increasing heart beat. Masthanaiah et al (1978) found a diel rhythmic activity of lipase in the scorpion peaking at 20.00 h with a minimum at 8.00AM.…”
Section: Phosphorylasementioning
confidence: 99%